Trends in higher-education participation in Northern Ireland - Osborne, R.D.; Miller, R.L.; Cormack, R.J.; Williamson, A.P. (Economic & Social Studies, 1989)
This paper is concerned with the analysis of a recent cohort of higher education entrants from Northern Ireland. It examines the social and educational characteristics of these entrants in the light of data relating to previous entry cohorts and considers a number of policy issues arising from the analysis.
Keywords: Education - Northern Ireland; Demographics